A Matching Theory of Entrepreneurs' Tie Formation Intentions and Initiation of Economic Exchange - Vissa, Balagopal (Academy of Management Journal, 2011)
This study advances understanding of network dynamics by applying matching theory to examine entrepreneurs' intentions to add new ties to their personal networks. I propose that task complementarity and social similarity are important matching criteria that influence entrepreneurs' interpersonal tie formation intentions and test whether good matches increase the likelihood of the initiation of economic exchange ties. A novel research design using data from the business cards of new people met by a panel of Indian entrepreneurs reveals effects of matching and suggests that although entrepreneurs intentionally pursue valuable connections, they may be only partially accurate in their assessment of value.